Reframing Community Participation in Water Governance: A Comparative Sociology of Justice and Rural Water Access in Eastern and Central Indonesia - Suryadinata, Theofilus Apolinaris; Mundayat, Aris Arif; Zuber, Ahmad; Akbar, Rezza Dian; Rahmawati, Triana; Wulandari, Effieta Alfi (Jurusan Sosiologi FISIP Universitas Pattimura, 2026)
Limited access to clean water in rural Indonesia not only affects public health and well-being but also reflects structural challenges in water governance, particularly regarding the quality of community participation. This article examines the dynamics of community participation in water governance and its implications for equitable water access through a comparative study of rural areas in eastern and central Indonesia. The research was conducted in Cunca Lolos and Cunca Wulang villages (East Nusa Tenggara) and Banyuurip Village (Central Java) using a qualitative comparative case study design. Data were collected through field observations, in-depth interviews, focus group discussions, and document analysis, and were thematically analyzed by conceptualizing participation as a socially embedded process shaped by power relations and local institutions. The findings reveal that community participation largely remains functional, limited to technical and operational involvement without equal influence in planning and decision-making processes. This pattern occurs across differing ecological contexts, indicating that water inequality is driven less by natural scarcity than by institutional and social structures. Limited participation contributes to unequal water distribution, weak transparency, low collective ownership, and fragile management sustainability, positioning water governance as an arena for reproducing local power relations. The study reframes participation as a layered social practice rather than a normative program indicator, emphasizing that participation quality is central to achieving water justice in rural governance.